The global emergence of gay and lesbian politics : national imprints of a worldwide movement. - Adam, Barry D.; Duyvendak, Jan Willem; Krowel, André (Philadelphia : Temple University Press, 1999)
Fonds Suzan Daniel (FSD)
Engels
Monografie